(untitled) (Herald of Journalism, 2020)
In the world of business, PR managers and marketing professionals understand the importance to form and maintain strong and long-term relationships with consumers. What is vital to them is a consumer becoming a true fan of their products, as well as the brand becoming a connecting link between the product and a consumer. Attachment to the brand can be viewed as a mental variable that later impacts the constant and long-lasting reaction to the brand. One of the significant aspects of branding is related to the development of customer interest in product advertising. It is known that psychological methods of consumer management are used in advertising. The essence of these methods lies in the goal of doing everything possible to sell the product. The purpose of the study is to determine the role of psychological techniques in managing the relationship between the brand and the consumer. The article applies a review of the scientific and psychological literature, revealing the management of the relationship between the brand and consumer. Additionally, the results of the focus group interview were applied in order to determine the role of advertising and the use of psychological techniques in advertising to build a relationship between the brand and a consumer. An analysis of the scientific literature allows us to discuss on the relevance of the topic, whereas the results of the study are brought to practical recommendations aimed at improving the relationship between the brand and consumer. The value of the research is a summary of the knowledge and results of the modern research in the field of management between the brand and consumer, aimed at studying the parameters of choice, use and demonstration of the brand. The results of the study show that when managing the relationship between the brand and consumption, the psychological aspect and the emotional component appear to be important elements that are used by number of well-known brands to increase the consumption of their products and for competitiveness in a market economy. This study attempts to outline the features of advertising communications in promoting the brand in various categories of goods that affect formation and strengthening of relations between the brand and consumer.